2008
DOI: 10.1007/s10694-008-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Characteristics of Radiative Heat Transfer in Liquid Pool Fires

Abstract: This work numerically investigates the radiative flux and flame shape from heptane liquid pool fires with small to medium sized pool fires (14-38 cm), grid sizes, spectral bands and solid angles. Experimental results were originated for comparison. The results show that calculated flame shapes and radiative fluxes are in good agreement with the measurements for suitable grid resolution. Besides, the effect of the intermittency of a flame on thermal radiation was performed. Experimentally, a shield was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…The computational domains were composed by rectangular and isotropic grid cells that varied according to the experimental tests simulated. For simulations involving buoyant plumes, the non-dimensional expression * / is recommended to measure how well the fluid flow field is resolved as follows (Lin et al, 2010):…”
Section: Mesh Resolutionmentioning
confidence: 99%
“…The computational domains were composed by rectangular and isotropic grid cells that varied according to the experimental tests simulated. For simulations involving buoyant plumes, the non-dimensional expression * / is recommended to measure how well the fluid flow field is resolved as follows (Lin et al, 2010):…”
Section: Mesh Resolutionmentioning
confidence: 99%
“…Thus, the jet flames are at the beginning of the transition regime from buoyant to momentum-dominated flames. In this sense, the nondimensional expression defined by Lin et al [57] for buoyant and transition regimes can be applied:…”
Section: Cell Size and Computational Domainmentioning
confidence: 99%
“…22 FDS can deliver accurate predictions for mean values of temperature and axial distributions. [23][24][25][26][27] Xin et al 24 studied the methane diffusion flame of 7.1 cm burner and helium plume of 7.3 cm burner size to check the applicability of mixture fraction based combustion model employed in FDS to the real-life fire scenario. They observed that FDS can qualitatively capture instantaneous fire structures and quantitatively reproduce the averaged scalars and velocities.…”
Section: Introductionmentioning
confidence: 99%
“…22 FDS can deliver accurate predictions for mean values of temperature and axial distributions. 2327…”
Section: Introductionmentioning
confidence: 99%